Failure to clear elevated lactate predicts 24-hour mortality in trauma patients. Issue 4 (October 2015) - Dezman, Zachary D.W.; Comer, Angela C.; Smith, Gordon S.; Narayan, Mayur; Scalea, Thomas M.; Hirshon, Jon Mark
<x xml:space="preserve">Abstract</x> BACKGROUND Lactate clearance is a standard resuscitation goal in patients in nontraumatic shock but has not been investigated adequately as a tool to identify trauma patients at risk of dying. Our objective was to determine if trauma patients with impaired lactate clearance have a higher 24-hour mortality rate than patients whose lactate concentration normalizes. METHODS A retrospective chart review identified patients who were admitted directly from the scene of injury to an urban trauma center between 2010 and 2013 and who had at least one lactate concentration measurement within 24 hours. Transfers, patients without lactate measurement, and those who were dead on arrival were excluded. Of the 26, 545 screened patients, 18, 304 constituted the initial lactate measurement population, and 3, 887 were the lactate clearance cohorts. RESULTS Initial lactate had an area under the receiver operating characteristic curve of 0.86 and 0.73 for mortality at 24 hours and in the hospital, respectively. An initial concentration of 3 mmol/L or greater had a sensitivity of 0.86 and a specificity of 0.73 for mortality at 24 hours. The mortality rate among patients with elevated lactate concentrations (n = 2, 381; 5.6 [2.8] mmol/L) that did not decline to less than 2.0 mmol/L in response to resuscitative efforts (mean [SD] second measurement, 3.7 [1.9] mmol/L) was nearly seven times higher (4.1% vs. 0.6%, p < 0.001) than among those with an elevated concentration (n = 1, 506, 5.3 [2.7] mmol/L) that normalized (1.4 [0.4] mmol/L). Logistic regression analysis showed that failure to clear lactate was associated with death more than any other feature (odds ratio, 7.4; 95% confidence interval, 1.5–35.5), except having an Injury Severity Score (ISS) greater than 25 (odds ratio, 8.2; 95% confidence interval, 2.7–25.2). CONCLUSION Failure to clear lactate is a strong negative prognostic marker after injury. An initial lactate measurement combined with a second measurement for high-risk individuals might constitute a useful method of risk stratifying injured patients. LEVEL OF EVIDENCE Prognostic study, level III.